Upaya Hukum Perlindungan Batik Tegalan Sebagai Potensi Indikasi Geografis - Muhammad Bagus Setiawan; Simona Bustani (Universitas Pancasakti Tegal, 2026)
Indonesia has a cultural diversity that gives birth to various regional products, one of which is Tegalan Batik from Tegal Regency which has high economic value. This batik has the potential to obtain Geographical Indication protection based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This study aims to determine whether Tegalan Batik is worthy of being registered as a Geographical Indication Intellectual Property and obtaining legal protection. This study uses a normative method with a descriptive research nature, using secondary data supported by interviews with both parties, data collection through analyzed literature studies and drawing conclusions using deductive methods. Based on the results of the study, it is known that based on Article 1 number 6 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications, Tegalan Batik is worthy of obtaining Geographical Indication protection because it has sufficiently fulfilled the elements as a Geographical Indication because it has a reputation, quality, and characteristics that are influenced by geographical environmental factors, both natural and human factors. So by obtaining legal protection, it provides a sense of security needed by craftsmen and the community to enjoy their legal rights and can prevent external threats.